The effect of cheese intake on osteoarthritis: a Mendelian randomization study - Song Wen; Zehan Huang; Bin Zhang; Yuqing Huang (Archives of Medical Science)
Introduction Osteoarthritis (OA) is a debilitating chronic disease with a high prevalence, characterized by progressive degeneration of articular cartilage that leads to joint dysfunction, pain, and disability. Observational studies investigating the link between cheese intake and OA have yielded inconclusive results and may be susceptible to confounding.